Proceso de atención de enfermería a escolar de 5 años con Síndrome Nefrótico. - Crespo Vizueta, Sasha Michelle (2021)
The present clinical case that was performed at the Alfredo Noboa Montenegro Hospital, belongs to a male patient, 5 years old, with a diagnosis of Nephrotic Syndrome, it is used to define various disorders or diseases that occur in the kidneys, usually based on a set of small blood vessels that contain the kidneys, these small blood vessels help filter toxins and excess water in the blood due to prominent manifestations of proteinuria in urination (urine). The purpose of this clinical case is to implement the correct intervention measures by the nursing staff and to point out the discomfort caused by the patient's pathological condition. Information was obtained since his arrival at the hospital unit about his pathology and how long he has been suffering from it, in order to perform the nursing assessment according to Marjory Gordon's functional patterns and to provide the relevant care according to the patient's needs. After the interventions carried out, improvements in the patient's health have been seen and he is calm and encouraged with the results obtained so far.